Attending to assessment problems of practice during community-centered professional development - Siegel, Marcelle A.; Cite, Suleyman; Muslu, Nilay; Murakami, Christopher D.; Burcks, Shannon M.; Izci, Kemal; Nguyen, Phuong D. (Elsevier BV, 2019)
Abstract This study focused on problems of practice of science teachers participating in a two-year, community-centered professional development and assessment design program. We examined problems of practice related to assessment. To explore this type of problem of practice, we employed an intrinsic case study approach and a community of practice theoretical lens. Five high school chemistry teachers and eight university personnel acted as participants in the study. In addition to several secondary data sources, the primary data sources included: a) 12 audio recordings of the collaborative meetings (over 28 h), b) 18 video recordings of teachers’ assessment practice (over 31 h), and c) 42 discussion board postings online. Three themes emerged based on iterative cycles of analysis for problems of practice for teachers’ assessment: 1) meeting students where they are, 2) students who do understand, and 3) the culture of the classroom. Our investigation contributes to the limited literature on ways teachers problematize and refine the enactment of classroom assessment.
Keywords: 4. Education; 16. Peace & justice